ANALISIS LINGKUNGAN BISNIS EKSTERNAL SEKOLAH MUSIK DENGAN MENGGUNAKAN ANALISIS PEST DAN FIVE FORCES PORTER - Andrijana Kusuma, Kanggep; Prama Agusmar Yahya, Angga; Naufal, Alman; Maulani, Shanti; Ratna Juwita Sari, Deassy (Jurnal Sistem Informasi Galuh, 2026)
Analysis of pest and five forces porter in planning the company's system and strategy in business competition is very necessary. Where external business environment analysis can help as a reference in planning the achievement of a company's strategic goals. This research aims to identify factors influencing business competition among music education institutions using Porter's Five Forces analysis and PEST analysis, which will serve as input for music schools when developing strategies to increase their competitiveness. In this study, the author observed a music school to examine data and documents, and also interviewed the owner to gather the necessary information. The final results of the PEST analysis include an analysis of external factors affecting music schools. The analysis results from Porter's Five Forces analysis include analysis of new entrants, substitute products, consumers, suppliers, and industry competition. PEST and Porter's Five Forces analysis within the music school business will be helpful in identifying external factors affecting music schools, industry competition, new entrants, and substitute products. The recommendation from this research is that the results of the PEST analysis and Porter's Five Forces analysis are expected to provide input regarding external factors that may impact music schools, along with an analysis of industry competition. This will significantly support companies in implementing Information Systems and Information Technology planning.